Educational evaluation and teachers' perceptions in Ecuador - Martínez-Lalangui, Juan Alfredo; Andrade-Vargas, Lucy; Salazar-Vallejo, Geovanna (Journal of Ecohumanism, 2024)
Educational assessment and teachers' perceptions are intrinsically intertwined in the educational environment. In this framework, teachers' beliefs and opinions about teaching and learning shape both their approach to student assessment and their interpretation of the results obtained. The article analyzes teachers' perceptions of the evaluative culture in relation to their beliefs, attitudes and ethical values. The present study, of an interpretivist nature, assumes a mixed methodological route, with a sequential exploratory design, supported by field techniques such as the survey and the interview. The teachers' results show a positive self-perception of their student-centered assessment skills and ethical values; however, variability is observed in the use of traditional assessment strategies and in attitudes towards summative assessment, which denotes a diversity of approaches and opinions regarding educational assessment in this context.